A cross‐sectional study of patient and provider perception of "cure" as a goal of cancer surgery. Issue 6 (3rd October 2016) - Winner, Megan; Wilson, Ana; Yahanda, Alexander; Kim, Yuhree; Pawlik, Timothy M.
Abstract : Background and Objective: Patients with advanced cancer often misperceive the purpose and likely effectiveness of cancer treatments. The aim of this study was to characterize patient and provider perceptions in the setting of surgery for potentially curable cancer. Methods: One hundred and six patient‐surgeon dyads were surveyed about their expectations for upcoming surgery. Items scored using a Likert scale were compared using the Wilcoxon signed‐rank test. Results: Patients and surgeons reported excellent communication and shared decision‐making. Patients more often than surgeons perceived that surgery was "Likely" or "Very Likely" to cure their cancer (86.0% vs. 72.0%, P  = 0.011), extend their lives (94.0% vs. 82.0%, P  = 0.007), and relieve cancer‐related symptoms (65.0% vs. 35.0%, P  < 0.001). Patients less often felt that surgery would be associated with complications (33.0% vs. 48.0%, P  = 0.016). Over half (53.9%) of patients believed that they were more likely to experience surgical cancer cure compared with someone else with the same diagnosis while 70.8% of surgeons declared a patient's relative chances of surgical cure "the same." Conclusions: Patients with resectable lung and gastrointestinal cancers have more optimistic perceptions about the outcomes of an upcoming surgery than their surgeons, even in a setting of good communication and shared decision‐making. J. Surg. Oncol. 2016;114:677–683 . © 2016 Wiley Periodicals, Inc.